"Como ver o mundo do outro lado. Longe, mas real.": uma análise de "Dragon Age: origins" e "Dragon Age II" sob o prisma da queer temporality - Maria de Sa Frizzera Scardua (2019)
The history of video games stars 60 years ago, keeping with the immemorial human tradition of playing in the incipient digital platforms. In the 2010s the video game industry is one of the biggest in the entertainment field, generating billions of dollars in its various sectors, and especially in its Triple A games. During the short but fast-paced history of video games, those big budget titles acquired positions and status that created conventions within the aesthetic and poetic interpretations of the media as a whole. This dissertation makes an invitation to analyze those games through J. Halberstams queer temporality , a perspective that celebrates the appreciation and creation of spaces and times outside of the traditional ways of seeing. To that end it presents a detailed analysis of the the first two games of the Dragon Age franchise - Dragon Age: Origins and Dragon Age II - under queer temporality as fundamental for the deepest understanding of these games universe and wider and more conscious gameplay experiences.